(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the technological significance, usage principles, application conditions, and efficiency indicators of anti-scalant agents in the process of obtaining demineralized water at the Shurtan Gas Chemical Complex. Based on analyses, practical experiments, and technological requirements, information on the optimal dosage and working mechanism of these reagents is provided.